New troglomorphic Arrhopalitidae (Collembola: Symphypleona) from the Western Caucasus - Vargovitsh, Robert S. (Zootaxa, 2012)
Two highly troglomorphic species of the family Arrhopalitidae Stach, 1956 are described from the caves of the Western Caucasus: Arrhopalites macronyx sp. nov. and Troglopalites stygios gen. nov. sp. nov. They inhabit epineustonic and hygropetric zones of subterranean realm and are characterized by much elongated claws, long antennae with annulations between subsegments of the fourth antennal segment, absence of strongly spine-like setae on dens, presence of accreted teeth on posterior lamellae and well-developed anterior lamella of mucro. Together with some diagnostic characters of the genus Arrhopalites Börner, 1906, Troglopalites gen. nov. shows reduced chaetotaxy of the sixth abdominal segment, almost linear trichobothrial pattern on great abdomen, and plurichaetosis on the forth antennal segment. Remarks on re-examination of trichobothrial complex chaetotaxy of Arrhopalites karabiensis Vargovitsh, 2009 and A. peculiaris Vargovitsh, 2009 from the Crimean caves are also included.